Lessons learned from imaging mouse ovarian tumors: the route of probe injection makes a difference - Han, Myung Shin; Tung, Ching-Hsuan (Quantitative Imaging in Medicine and Surgery; Vol 4, No 3 (June 01, 2014): Quantitative Imaging in Medicine and Surgery, 2014)
Patients with ovarian cancer often develop small metastatic lesions in their peritoneal cavities. Fluorescent-imaging probes that can highlight these small lesions have significant value for guiding procedures and treatment decisions. In this animal study, we demonstrated that intraperitoneal (IP) delivery of a protease-sensitive fluorescent probe resulted in the labeling of all tumors regardless of their sizes with low background signals in organs. Conversely, intravenous (IV) injections of the probe resulted in high signals in most organs and large tumors (>5 mm) but not in any of the small lesions (